EFEKTIVITAS MEDIA LUMIO DALAM LAYANAN BIMBINGAN KLASIKAL TERHADAP CAREER SELF EFFICACY DAN PENGAMBILAN KEPUTUSAN KARIER SISWA SMK - giyar indra; Nursalim Mochammad; Tri Retno Hariastuti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Based on tracer study data from SMKN 1 Gempol, 62.8% (349 out of 557) students have not yet entered the workforce. Hesitation and the lack of digital guidance and counseling media pose career challenges. The purpose of this study was to determine the effectiveness of Lumio media on students' career self-efficacy and career decision-making. The research used a quantitative quasi-experimental approach with a pretest-posttest nonequivalent control group design. Purposive sampling was used. Data analysis used paired t-tests, ANOVA, and Pearson Product Moment Correlation Tests at a significance level of 0.05. The results of the study in the experimental class showed that the average CSE score increased from 73.90 (pretest) to 84.40 (posttest) with a paired t-test result of Sig. <0.001 and a Cohen's d effect size of 1.34 (large category). The average PKK score also increased from 73.50 to 81.83 with Sig. < 0.001 and effect size Cohen's d = 0.74 (moderate category). In contrast, in the control class, the increase in CSE was not significant (Sig. = 0.326), while PKK showed significant (Sig. < 0.001). The results of the ANOVA test showed a significant difference between the experimental class and the control class (Sig. < 0.001). The results of the Pearson correlation test showed a positive and significant relationship between CSE and PKK in the experimental class with a value of r = 0.700 (Sig, < 0.001). It can be concluded that lumio media is effective in improving students' CSE and PKK.